أثر نظرية المقاصد الشرعية في الإفتاء : دراسة تحليلية مقارنة بين فتاوى الشيخ محمد بن صالح العثيمين والشيخ يوسف القرضاوي - مارلينج، ناصر الحق (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2018)
This research deals with “The Impact of Maqasid al-Shariah theory in the fatwa and contemporary ijtihad: A comparative analysis between the fatwas of Shaykh Muhammad Saalih al-Othaimeen and Sheikh Yusuf al-Qaradawi”. This study examines how the contemporary ijtihad and issuance of fatwas based on the Maqasid al-Shariah in its dimensional theory as general concepts, principles and rules of ijtihad. The researcher relied on inductive method in the preparation of the plan of the study as required for writing research in the collection of scientific material, critical analysis of the concepts from two sheikhs based on the Maqasid al-Shariah in fatwa, and comparative methods between their fatwas in terms of how they were inferred by Maqasid al-Shariah. The first chapter of this study deals with research methodology. In the second chapter, the concept of maqasid, its foundations and its impact on fatwa and contemporary ijtihad were covered. The third chapter discusses about the analysis of maqasid al-shariah in the views of the two sheikhs in terms of the most prominent characteristics and the methodological rules for both of them. The fourth chapter, discusses the impacts of the Maqasid al-Shariah in the fatwa of the two sheikhs through the application of examples. This study resulted in a number of findings, including: That the most important fundamentals related to the theory of Maqasid al-Shariah in the fatwa and contemporary ijtihad are: al-fitrah (common sense), al-maslahah (interest), and al-ta'lil (reasoning); While the essential principles in it are: moderation (al-wasatiyah), the jurisprudence of easing (fiqh al-taysir), the jurisprudence of priorities (fiqh al-awlawiyat), consideration of the consequences of things (i'tibar al-ma'alat), the jurisprudence of muwazanat and tarjih, the reduction of intolerance and differences through collective fatwas. Among the most prominent characteristics and the rules in the methodological fatwa of sheikh Ibn Othaimeen are: focus on the creed of the Salaf scientifically, practice and belief, adhering to the texts and thoroughness to ensure the validity of the proposition, attention to maqasid al-sharia and consideration of consequences of ease and difficulties, and understanding the reality and events. While the most important characteristics and the rules in the fatwa of Sheikh Yusuf al-Qaradawi are: the moderation of Islam as a whole, the contemporary revival of ijtihad, the renewal of Islamic law, and the contemporary fatwa. Among the most prominent characteristics which he expands in it include taking the middle road (al-tawassut) and understanding texts based on the general purpose of the law. This study proves the effects of considering Maqasid al-Shariah in the fatwa by the two sheikhs through a comparison between their fatwas in terms of worship, financial transactions, family law, and political realities. As a result of the comparison, both of them represent a special model that could be emulated in the ijtihad maqasidi. And his influence was apparent when the maqashid theory can accommodate more than one model fatwa and ijtihad by accommodating differences or diversity of thoughts as well extenuating circumstances.